The effect of increasing the state pension age to 66 on labour market activity - Jonathan Cribb; Carl Emmerson; Laurence O'Brien (Institute for Fiscal Studies (IFS), 2022)
We study the effect of an increase in the UK state pension age from 65 to 66, a high level internationally, on labour market activity. Despite there being limited financial incentives to retire at the state pension age, we find large effects: the employment rate of 65-year-olds increased by 7.4 percentage points for men and 8.5 percentage points for women due to the reform. The employment response is driven disproportionately by full-time workers and self-employed men, and is larger for those with lower levels of education and those living in the most deprived areas of the country.
Keywords: H55; J21; J26; 330; Early retirement age; labour supply; policy reform; retirement